Spatiotemporal Processing of Bimodal Odor Lateralization in the Brain Using Electroencephalography Microstates and Source Localization - Hucke, Christine Ida; Heinen, Rebekka Margret; Pacharra, Marlene; Wascher, Edmund; van Thriel, Christoph (Frontiers in Neuroscience, 2021)
The neuronal cascade related to the perception of either purely olfactory or trigeminal airborne chemicals has been investigated using electroencephalography (EEG) microstate analyses and source localization. However, most airborne chemicals are bimodal in nature encompassing both properties. Moreover, there is an ongoing debate if there is one dominant nostril which could be investigated using these multichannel EEG methods. In this study, 18 right-handed healthy participants (13 females) were monorhinally stimulated using an olfactometer with the bimodal component acetic acid during continuous EEG recording. Participants indicated the side of stimulation, the confidence in their decision, and rated the strength of the evoked perception. EEG microstate clustering determined four distinct maps and successive backfitting procedures and source estimations revealed a network which evolved from visual-spatial processing areas to brain areas related to basic olfactory and trigeminal sensations (e.g. thalamus, cingulate cortex, insula, parahippocampal and pre-/postcentral gyri) and resulted in activation of areas involved in multisensory integration (e.g. frontal-temporal areas). Right-nostril stimulation was associated with faster microstate transition and longer involvement of the superior temporal gyrus, which was previously linked to chemical localization and provides evidence for a potential nostril dominance. The results describe for the first time the processing cascade of bimodal odor perception using microstate analyses and demonstrate its feasibility to further investigate potential nostril dominance.